Spatial and Temporal Effects of Whale Watching on a Tourism-Naive Resident Population of Bottlenose Dolphins (Tursiops truncatus) in the Humboldt Penguin National Reserve, Chile - Toro, Frederick; Alarcón, Jaime; Toro-Barros, Bárbara; Mallea, Gabriela; Capella, Juan; Umaran-Young, Clara; Abarca, Paulette; Lakestani, Nelly; Peña, Claudia; Alvarado-Rybak, Mario; Cruz, Franco; Vilina, Yerko; et al. (Frontiers in Marine Science, 2021)
Standardized measures of behavior can be powerful tools for assessing the impact of Whale Watching (WW) activities on natural populations of cetaceans. To determine the possible impact of tourism on dolphins between a period T1 without WW (1989 - 1992) and T2 with WW boat (2010 -2020) we examined the changes in the rate of surface behaviors, the group size of long-time resident bottlenose dolphins living in the in the waters of the Humboldt Current off Chile, and for T2 compare this differences between two locality's Punta de choros (PDC) and Chañaral de aceituno (CDA). We observed a significant decrease in group size of the resident population and in the frequency of surface events associated with the absence and presence of tourism. For T2 we observed significant differences for the frequency of surface events between CHA and PDC coves and differences in the frequency of the surface events in different hours of the day, this was associated with the number of vessels in the moment of the encounter. In addition, we observed for T2 that the instantaneous response of the dolphins to the presence of tourist vessels, being avoidance was the most observed, and approach the less observed. The number of vessels present in each dolphin encounter was the most important variable that our model gives as explanatory to these differences. These results show that tourism vessels have a significant impact on dolphin behavior and sociability, where for the same population of dolphins have spatial and temporal differences in his response to a different impact of tourism. Further studies are needed to establish whether changes in the rate of surface behaviors are associated with higher levels of stress in dolphins and with effects on their health and reproductive success in the long term.